The Effect of Using L-Arginine as a Feed Additive on Testosterone Levels in Ross 308 Broiler Breeder Roosters: The Effect of Using Arginine on Testosterone Level in Roosters of Broiler Breeders (Journal of Hama University, 2026)
This study was conducted to demonstrate the effect of using arginine as a dietary supplement on the functional performance of the reproductive system in broiler breeder roosters. For this study, 60 broiler breeder roosters of the Ross 308 strain were used, and the birds were divided into four groups. The control group included 15 birds fed according to the recommendations of the strain's production company. Group S1 included 15 birds fed according to the company's recommendations with the addition of arginine at a rate of 1 kg per ton of feed. The second group, S2, also included 15 birds, with arginine added to the feed mixture at a rate of 2 kg per ton of feed. The fourth group, S3, included 15 birds, with arginine added at a rate of 4 kg per ton of feed.Blood samples were taken to examine testosterone levels at four different time points: at the beginning of the experiment, then after 15, 30, and 60 days from the start of the experiment. The results showed an increase in testosterone levels, sperm motility, and an improvement in seminiferous tubule diameter in groups S2 and S3 compared to the control group and S1.
Keywords: Key words: arginine- dietary supplement- functional performance- reproductive system- broiler breeder roosters- testosterone- sperm motility